MicroRNA‐186 alleviates oxygen‐glucose deprivation/reoxygenation‐induced injury by directly targeting hypoxia‐inducible factor‐1α. Issue 6 (24th March 2021) - Li, Shengnan; Wang, Yajun; Wang, Mengxu; Chen, Linfa; Chen, Shaofeng; Deng, Fu; Zhu, Peiyi; Hu, Weidong; Chen, Xinglan; Zhao, Bin; Ma, Guoda; Li, You
Abstract: Previous studies have suggested that microRNA‐186 (miR‐186) can be induced under hypoxic conditions, and is associated with apoptosis. This study was undertaken to explore the exact role of this microRNA (miRNA) in the apoptotic death of neurons during cerebral ischemic/reperfusion (I/R) injury. To model cerebral ischemia/reperfusion (I/R) injuries, we utilized a transient middle cerebral artery occlusion approach in rats, as well as a model of oxygen‐glucose deprivation/reoxygenation (OGD/R) in Neuro2a cells. We found that in both in vitro and in vivo models of cerebral I/R injuries, levels of miR‐186 were markedly decreased. When we overexpressed miR‐186, this was associated with a reduction in the apoptotic death of neuroblastoma cells in the OGD/R model system, whereas the opposite was true when this miRNA was instead inhibited. We further found miR‐186 to directly target hypoxia‐inducible factor 1α (HIF‐1α) by interacting with the 3′‐untranslated region of this mRNA. When we knocked down HIF‐1α, this partially overcame the apoptotic death of cells in response to OGD/R injury and associated miR‐186 downregulation. Our findings indicate that miR‐186 is able to reduce ischemic injury to neurons at least in part through downregulating HIF‐1α, suggesting that the miR‐186/HIF‐1α axis is a potential therapeutic target for the treatment of ischemic stroke.